2019
DOI: 10.1002/jhet.3759
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, reactions, and antimicrobial evaluations of new benzo[e][1,3]thiazine derivatives

Abstract: 4H-Spiro[benzo [d] [1,3]oxathiine-2,1′-cyclohexan]-4-one undergoes aminolysis with certain aromatic amines to give the respective 4-benzenesulfonamide, Ethyl benzoate, and 4-acetylphenyl of 4-oxospirobenzo[e][1,3]thiazine derivatives. The Schiff bases prepared by reacting Ethyl benzoate derivative 2a with aldehydes, undergoes cyclocondensation with thioglycolic acid yielding p-methoxyphenyl and 2-(thiophen-2-yl) thiazolidinone derivatives. Treatment of the benzoate derivative with hydrazine hydrate afforded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The highest activity was shown by compound 22 (Figure 16, Table 9) [27]. The hydrazide-hydrazone 23 obtained by Ewies et al exhibited promising antibacterial activity against S. aureus, S. typhimurium, and P. aeruginosa (Figure 17, Table 10) [28]. In 2020, Popiołek et al reported the synthesis and antimicrobial activity potential of hydrazide-hydrazones of 5-nitrofuran-2-carboxylic acid.…”
Section: Antimicrobial Activity 21 Antibacterial Activitymentioning
confidence: 99%
“…The highest activity was shown by compound 22 (Figure 16, Table 9) [27]. The hydrazide-hydrazone 23 obtained by Ewies et al exhibited promising antibacterial activity against S. aureus, S. typhimurium, and P. aeruginosa (Figure 17, Table 10) [28]. In 2020, Popiołek et al reported the synthesis and antimicrobial activity potential of hydrazide-hydrazones of 5-nitrofuran-2-carboxylic acid.…”
Section: Antimicrobial Activity 21 Antibacterial Activitymentioning
confidence: 99%
“…In continuation of synthesis of effective candidates in our laboratory as antimicrobial, antiviral, and anticancer agents [19][20][21][22][23]; we aim to conjugate Ibuprofen with phenyl alanine to be an effective agents as antiinflammatory and analgesic. Our strategy based on preparation of ibuprofen derivatives 1-17 starting from acid chloride 2 that may be expected to have biological activities (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…The carrageenan induced paw edema method used for evaluated the anti-inflammatory activity for 5 , 6 , 12 , 16 and 17 [21]. The compounds were examined at a 35 mg kg-1 body mass oral dosage and compared to the conventional medication ibuprofen at the same dose.…”
Section: Paw Edema Experimentmentioning
confidence: 99%
“…Among them, 1,3‐thiazine and their reduced forms dihydro‐1,3‐thiazine and tetrahydro‐1,3‐thiazine frameworks are privileged structural motifs found in many natural products [2] and biologically significant compounds [3] . For example, compounds containing such a skeleton exhibit antimicrobial, [3a] antibacterial, [3b,c] analgesic, [3d] antitumor, [3e] antihypertensive and NOS inhibiting activities [3f] . Moreover, well known antibiotics such as cephamycin and cephradine (cephalosporin class of β‐lactam antibiotics) contain 1,3‐thiazine scaffold (Figure 1).…”
Section: Introductionmentioning
confidence: 99%